Desarrollo de un manual de políticas de comunicación en el gobierno autónomo descentralizado del cantón El Guabo. - Sumba Torres, Lorena Elizabeth (2016)
The development of a communication policy manual is the work developed as a degree project during the months of May, June, July and August where the knowledge acquired during the eight semesters at the Technical University of Machala was applied. The Autonomous Decentralized Government (GAD) of Cantón El Guabo was selected as the site for the study, where a research was carried out on the communication practices of the institution through the qualitative method, as the first step was to recognize the policies Of communication that the institution applies, the same that are not documented or officialized due to the lack of a Communication Policy Manual. In the second part of the diagnosis, the current situation of institution was determined in reference to the communicational practices. In addition, communication channels established among them were identified: the use of telephone calls and e-mails as the main ones of internal communication; The social network Facebook, MCTV Channel 5 and Public Radio El Guabo in external communication that act immediately.